Biodegradation - Engineering and Technology 2013
DOI: 10.5772/56143
|View full text |Cite
|
Sign up to set email alerts
|

Emulsification of Hydrocarbons Using Biosurfactant Producing Strains Isolated from Contaminated Soil in Puebla, Mexico

Abstract: Among Mexico's main riches are its oil and the great expanses of land used to grow food. A large number of pipelines pass through Mexico's agricultural region carrying diesel, gasoline or crude oil, however, lack of maintenance of the pipeline installations, fuel theft, vehicle transport and even the topographical, terrain and hydrological conditions of the site cause a high incidence of contamination. Petrolic activities have generated extensive pollution of soils worldwide, mainly in those regions where petr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…bernadiae could have mineralised diesel the most because the isolates produced higher biosurfactants in diesel compared to other contaminants. This tallies with the study of Prez-Armendriz et al 23 who, although worked on bacteria, identified that PAHs degradation rates were high as a result of the high biosurfactant production by their isolates. The reason for A. slackii mineralizing aviation fuel the most is not farfetched; aviation fuel contains the least aromatic hydrocarbons when compared to other contaminants.…”
Section: Kinetic Modelingsupporting
confidence: 83%
“…bernadiae could have mineralised diesel the most because the isolates produced higher biosurfactants in diesel compared to other contaminants. This tallies with the study of Prez-Armendriz et al 23 who, although worked on bacteria, identified that PAHs degradation rates were high as a result of the high biosurfactant production by their isolates. The reason for A. slackii mineralizing aviation fuel the most is not farfetched; aviation fuel contains the least aromatic hydrocarbons when compared to other contaminants.…”
Section: Kinetic Modelingsupporting
confidence: 83%
“…However, one should not dismiss the fact that plants contain monooxygenases of cytochrome P450 (CYP8D1), which increase their resistance to organic contamination (Daudzai et al 2018). Furthermore, the activity of biosurfactants can be moderated by phenolic compounds used preferentially as a source of carbon (Pérez-Armendáriz et al 2013). This was probably the reason why the interaction of BPA at the highest dose and rhamnolipid 90 brought the desired result.…”
Section: The Effect Of Bpa On Spring Barleymentioning
confidence: 99%
“…All cultures were incubated at room temperature. After four sub-cultures, the diesel was replaced by the target PAHs (pyrene, naphthalene, and phenanthrene) in the Lebac medium, which was the only carbon source available for the growth and maintenance of the microorganisms, at a concentration of 5 mg L −1 [14,22]. The microbial consortium was reserved for the bioremoval experiment.…”
Section: Methodsmentioning
confidence: 99%
“…However, working with microbial consortia requires an adaptation period, which consists of pre-enrichment and enrichment phases that depend on the compound analyzed, and the microorganisms’ ability to degrade the target PAHs at contaminated sites must be proven [13,14,15,16]. In the present study, ore waste was used because it commonly contains microorganisms that have survived mining contaminants (including PAHs) and that may have the capacity to remove certain organic compounds.…”
Section: Introductionmentioning
confidence: 99%